Chosen Vascular Risk Markers in Pseudoexfoliation Syndrome: An Age-Related Disorder - Hanna Lesiewska; Agnieszka Łukaszewska-Smyk; Grażyna Odrowąż-Sypniewska; Magdalena Krintus; Aneta Mańkowska-Cyl; Grażyna Malukiewicz (Journal of Ophthalmology)
Purpose. To evaluate lipids and C-reactive protein serum levels in patients with pseudoexfoliation syndrome (PEX) in the Polish population. Methods. 96 patients were studied with PEX and 79 control subjects. Total cholesterol, triglycerides, high-density lipoprotein (HDL)-cholesterol, low-density lipoprotein (LDL)-cholesterol, non-HDL-cholesterol and CRP serum levels, and TG/HDL-C and TC/HDL-C indexes were assessed. Results. There were no significant differences in concentration of lipids and values of TC/HDL-C, TG/HDL-C, and non-HDL-C between PEX and control groups. High-sensitivity C-reactive protein was not increased in patients with PEX. Conclusions. Our results cast doubt on the opinion on the possible PEX and vascular diseases relation. Further studies on this subject are mandatory.